Evaluation of Cardiomegaly in Dogs Using the Manubrium Heart Score Method and Determination of Its Diagnostic Accuracy in Comparison with the Vertebral Heart Score - Bengü Bilgiç; Onur İskefli; Michela Pugliese; Mehmet Erman Or (Veterinary Sciences, 2025)
Vertebral Heart Score (VHS) is one of the commonly used methods for detecting cardiomegaly in dogs. However, this method has diagnostic limitations due to factors such as breed variations, orthopedic disorders, anatomical anomalies, and operator-dependent subjectivity. The aim of this study was to evaluate the diagnostic utility of the Manubrium Heart Score (MHS) as an alternative to VHS in the assessment of cardiomegaly in dogs. A total of 490 dogs were classified and grouped based on body weight and cardiac health status. On the right lateral thoracic radiographs, MHS was calculated as the ratio of manubrium length (ML) to the sum of the long-axis heart length (cLAL) and short-axis heart length (cSAL). Similarly, VHS was determined. A positive correlation between VHS and MHS, as well as between ML and cSAL/cLAL, were observed in all groups except for the group of medium sized dogs with heart diseases. No correlations were found between MHS and LA or the LA/Ao ratio. In pairwise comparisons of VHS and MHS between heart-diseased and healthy dogs, the mean VHS showed a statistically significant difference in heart-diseased dogs (p < 0.001), and not across all groups (p > 0.05). MHS may not consider a useful method as an alternative to VHS.